KEBIJAKAN ZERO TOLERANCE POLICY TAHUN 2018 - 2019 STUDI KASUS IMIGRAN AMERIKA LATIN - Ratra Lovianitra Anugrah; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research aims to explain the causes of the emergence of policies that explicitly reject Latin American immigrants during the leadership of President Donald Trump, even though the United States managed to overcome the immigrant crisis that occurred in the previous leadership. Migration flows continued to decline until Trump's time, but he still issued a fairly tough policy against immigrants by implementing Zero Tolerance Policy. This policy had an impact on immigrants that crossing the United States-Mexico border, namely Latin American immigrants, which led to many children being forced to separate from their parents, sparking protests and finally being stopped by executive order.The Adaptive Model by James N. Rosenau is the theory used in analyzing the problem in this research. The foreign policy taken by a country is the result of changes, both from inside and outside the country. Change is the center of adaptation, so in this theory foreign policy is caused by three variables, leadership, internal change and external change. The policy was taken as a response to changes in order for the essential structure adaptable and maintain internal values.The release of the Zero Tolerance Policy which rejected the entry of Latin American immigrants as a result of the leadership change that occurred in the United States. President Donald Trump, who sees external influences as threatening the essential structure of his country, takes steps to defend internal values. This policy adapts the intransigent pattern, which is influenced by transactionalism and the Jacksonian style, so in the end the policies taken become ineffective.Keywords: America First, Donald Trump, United States of America, Zero Tolerance Policy.